The Importance of Uric Acid in the Development of Cardiovascular Diseases - Xamraeva Gulnora Ilyosovna (Central Asian Journal of Medical and Natural Science, 2024)
Cardiovascular disease (CVD) is a common name for diseases of the heart and blood vessels. Currently, these diseases are one of the main causes of death and disability worldwide. Currently, several studies have emphasized hyperuricemia as an independent risk factor for CKD. According to the literature, hyperuricemia occurs in 2% of the US population, 17% in France, 7% in Spain, and 19.3% in Russia. This article provides information on the importance of uric acid in the development of cardiovascular diseases.